Hybrid Learning Model Through SIPEJAR Content as Learning Innovation in History Education Research Courses - Wahyu Djoko Sulistyo; Riki Pratama (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2023)
This research and development aim to generate a hybrid learning model by incorporating SIPEJAR UM content. This collaboration aims to foster innovation and adaptation to the changing times and the digitalization era in education. The hybrid learning model, implemented in the History Education Research course, combines face-to-face and online learning. This approach enables a blended learning process that combines the advantages of both methods. The research method utilized in this research and development study is the Dick and Carey model. The data for this article was gathered through observations, interviews, and questionnaires distribution to students and lecturers. The outcome of this research and development study is a collaborative hybrid learning model that incorporates SIPEJAR UM through the provision of learning content in the History Education Research course.